Carob (Ceratonia siliqua L.) fruit hydro-alcoholic extract alleviates reproductive toxicity of lead in male mice: Evidence on sperm parameters, sex hormones, oxidative stress biomarkers and expression of Nrf2 and iNOS - Ali Soleimanzadeh; Mehdi Kian; Sajjad Moradi; Soraya Mahmoudi (Mashhad University of Medical Sciences, 2019)
Objective: Carob (Ceratonia siliqua L.) is an evergreen tree with fruits that have potent antioxidant activity. The aim of this study was to investigate alleviative effects of carob fruit hydro-alcoholic extract (CFHAE) against reproductive toxicity induced by lead (Pb) in male mice. Material and Methods: Forty-two NMRI adult male mice were randomly categorized into 7 groups (N=6). Group I was the control group and received no treatment. Group II was the sham group and received 0.2 ml distilled water per day. Group III (Pb group) received Pb acetate 1000 ppm/kg/day. Groups IV and V received CFHAE 500 and 1000 mg/kg/day, respectively. Groups VI and VII received both Pb 1000 ppm/kg/day and CFHAE at doses of 500 and 1000 mg/kg/day, respectively at the same time. The groups were treated by gavage. After 35 days, sperm parameters (count, motility, morphology, viability, DNA damage, and teratozoospermia index), total antioxidant capacity (TAC), reduced glutathione content (GSH), antioxidant enzymes (SOD, CAT, and GPx) activity, MDA levels, and sex hormones (FSH, LH, and testosterone) concentrations in serum, testicular expression of Nrf2 and iNOS genes and histopathological alterations were evaluated. Results: Our findings revealed that co-administration of CFHAE with Pb significantly (pNrf2 and iNOS genes compared with Pb group. Also, CFHAE ameliorated histopathological alterations in testis tissue caused by Pb. Conclusion: CFHAE can alleviate reproductive toxicity following Pb exposure in male mice.